Functional interplay between the transcription factors USF1 and PDX-1 and protein kinase CK2 in pancreatic β-cells - Sarah Spohrer (Nature Portfolio, 2017)
Abstract Glucose homeostasis is regulated by insulin, which is produced in the β-cells of the pancreas. The synthesis of insulin is controlled by several transcription factors including PDX-1, USF1 and USF2. Both, PDX-1 and USF1 were identified as substrates for protein kinase CK2. Here, we have analysed the interplay of PDX-1, USF1 and CK2 in the regulation of PDX-1 gene transcription. We found that the PDX-1 promoter is dose-dependently transactivated by PDX-1 and transrepressed by USF1. With increasing glucose concentrations the transrepression of the PDX-1 promoter by USF1 is successively abrogated. PDX-1 binding to its own promoter was not influenced by glucose, whereas USF1 binding to the PDX-1 promoter was reduced. The same effect was observed after inhibition of the protein kinase activity by three different inhibitors or by using a phospho-mutant of USF1. Moreover, phosphorylation of USF1 by CK2 seems to strengthen the interaction between USF1 and PDX-1. Thus, CK2 is a negative regulator of the USF1-dependent PDX-1 transcription. Moreover, upon inhibition of CK2 in primary islets, insulin expression as well as insulin secretion were enhanced without affecting the viability of the cells. Therefore, inhibition of CK2 activity may be a promising approach to stimulate insulin production in pancreatic β-cells.